Implant-based versus Autologous Reconstruction after Mastectomy for Breast Cancer: A Systematic Review and Meta-analysis. Issue 3 (11th March 2022) - Broyles, Justin M.; Balk, Ethan M.; Adam, Gaelen P.; Cao, Wangnan; Bhuma, Monika Reddy; Mehta, Shivani; Dominici, Laura S.; Pusic, Andrea L.; Saldanha, Ian J.
Abstract : Background: For women undergoing breast reconstruction after mastectomy, the comparative benefits and harms of implant-based reconstruction (IBR) and autologous reconstruction (AR) are not well known. We performed a systematic review with meta-analysis of IBR versus AR after mastectomy for breast cancer. Methods: We searched Medline, Embase, Cochrane CENTRAL, CINAHL, and ClinicalTrials.gov for studies from inception to March 23, 2021. We assessed the risk of bias of individual studies and strength of evidence (SoE) of our findings using standard methods. Results: We screened 15, 936 citations and included 40 studies (two randomized controlled trials and 38 adjusted nonrandomized comparative studies). Compared with patients who undergo IBR, those who undergo AR experience clinically significant better sexual well-being [summary adjusted mean difference (adjMD) 5.8, 95% CI 3.4–8.2; three studies] and satisfaction with breasts (summary adjMD 8.1, 95% CI 6.1–10.1; three studies) (moderate SoE for both outcomes). AR was associated with a greater risk of venous thromboembolism (moderate SoE), but IBR was associated with a greater risk of reconstructive failure (moderate SoE) and seroma (low SoE) in long-term follow-up (1.5–4 years). Other outcomes were comparable between groups, or the evidence was insufficient to merit conclusions. Conclusions: Most evidence regarding IBR versus AR is of low or moderate SoE. AR is probably associated with better sexual well-being and satisfaction with breasts and lower risks of seroma and long-term reconstructive failure but a higher risk of thromboembolic events. New high-quality research is needed to address the important research gaps.